2014
DOI: 10.1056/nejmoa1405584
|View full text |Cite
|
Sign up to set email alerts
|

One-Unit versus Two-Unit Cord-Blood Transplantation for Hematologic Cancers

Abstract: BACKGROUND Umbilical-cord blood has been used as the source of hematopoietic stem cells in an estimated 30,000 transplants. The limited number of hematopoietic cells in a single cord-blood unit prevents its use in recipients with larger body mass and results in delayed hematopoietic recovery and higher mortality. Therefore, we hypothesized that the greater numbers of hematopoietic cells in two units of cord blood would be associated with improved outcomes after transplantation. METHODS Between December 1, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
204
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(223 citation statements)
references
References 31 publications
15
204
2
2
Order By: Relevance
“…The merits of CBT are likely related to the low incidence of significant GvHD despite an increase in early mortality due to delayed hematopoietic and immunological recovery and graft failure after single CBT. [23][24][25] In the Holtan study, relative risks of GRFS events after CBT using mostly double units were approximately 2.0 compared with 6/6 HLA-matched sibling BMT, while hazard ratios after CBT compared with 6/6 HLA-matched sibling BMT in our study were lower at ranges between 1.20 and 1.35 regardless of patient age and disease risk. The difference between the studies could be accounted for by the lower risk of severe GvHD after single CBT compared with double CBT, 23,24 and by the lower risk of severe GvHD in the Japanese population compared with the Caucasian population.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…The merits of CBT are likely related to the low incidence of significant GvHD despite an increase in early mortality due to delayed hematopoietic and immunological recovery and graft failure after single CBT. [23][24][25] In the Holtan study, relative risks of GRFS events after CBT using mostly double units were approximately 2.0 compared with 6/6 HLA-matched sibling BMT, while hazard ratios after CBT compared with 6/6 HLA-matched sibling BMT in our study were lower at ranges between 1.20 and 1.35 regardless of patient age and disease risk. The difference between the studies could be accounted for by the lower risk of severe GvHD after single CBT compared with double CBT, 23,24 and by the lower risk of severe GvHD in the Japanese population compared with the Caucasian population.…”
Section: Discussionmentioning
confidence: 42%
“…[23][24][25] In the Holtan study, relative risks of GRFS events after CBT using mostly double units were approximately 2.0 compared with 6/6 HLA-matched sibling BMT, while hazard ratios after CBT compared with 6/6 HLA-matched sibling BMT in our study were lower at ranges between 1.20 and 1.35 regardless of patient age and disease risk. The difference between the studies could be accounted for by the lower risk of severe GvHD after single CBT compared with double CBT, 23,24 and by the lower risk of severe GvHD in the Japanese population compared with the Caucasian population. 4 Consistent with the Holtan study, 1 our study found that 6/6 HLA-matched sibling BMT was associated with higher GRFS compared with other graft sources.…”
Section: Discussionmentioning
confidence: 42%
“…17,24 Various strategies to approach these challenges are under study. The Blood and Marrow Transplant Clinical Trials Network conducted a study to determine whether children with hematological malignancies would have improved survival after a double UCBT, as compared with single UCBT (BMT-CTN 0501).…”
Section: Ucbt In Pediatricsmentioning
confidence: 99%
“…This study did not demonstrate an advantage for double UCBT in children where a single UCB provided an adequate cell dose. 24 ADULT UCBT Initial studies in single UCBT were hampered by delayed engraftment, leading to a high transplant-related mortality. 25 Outcome results have improved with better patient selection, better supportive care including growth factors, prophylactic and preemptive antiviral treatment and the choice of UCBT units with higher nucleated cell doses/kg ( Figure 1).…”
Section: Ucbt In Pediatricsmentioning
confidence: 99%
“…11,12 Although initial studies of double UCBT in adults appeared to be encouraging, 13,14 a recent prospective randomized trial of single versus double UCBT in children with hematological malignancies demonstrated no improved overall survival and a significant increase in severe acute GVHD and chronic GVHD in double cord transplant recipients. 15 New approaches are needed to accelerate the rapidity of neutrophil engraftment, and cellular immune reconstitution, reduce primary graft failure, decrease transplantrelated mortality and subsequently enhance OS following UCBT. This report summarizes a few new therapeutic approaches including ex vivo expansion, using engineered cord blood (CB) CD34 + cells expressing the Notch ligand Delta 1, co-culture expansion of mesenchymal progenitor cells (MPC) with CB progenitor cells, the addition of third party human placentaderived stem cells (HPDSCs) with single or double UCBT and the expansion and utilization of CB-derived natural killer (NK) cells.…”
Section: Introductionmentioning
confidence: 99%